Pemanfaatan Aplikasi Slims ( Senayan Library Manajemen System ) Pada Perpustakaan - Fadlina; Garuda Ginting; Ikwan Lubis (JPM: Jurnal Pengabdian Masyarakat, 2022)
SMA Negeri 1 STM Hilir is located at Jl. Education Hamlet I Alun Kenas, Mt. Rintih, Sinembah Tj. Muda Hilir, Deli Serdang Regency. SMA Negeri 1 STM Hilir, is now starting to improve, changes are clearly visible starting from the school building or physique to improving the quality of both teaching teachers and students. This was also conveyed by Dra Elvia Nas MPd as the principal of SMAN 1 STM Hilir who is domiciled on Jln Pendidikan Dusun 1, Talun Kenas Village, STM Hilir Sub-District, Deli Serdang Regency, when met by the media crew recently. Elvia explained to the media that the school she leads has 10 local schools and 380 students. As a paradigm, she always does her best for the progress of students at this school, especially avoiding drugs, which are enemies of the state, she concluded. Monitoring in the field also shows that the school buildings are physically much better than before including the cleanliness and use of the park, the students are also seen participating in the learning process with full comfort as well as the teachers there. And what is no less important is the use of the library arranged in such a way for the progress of the school. Students are introduced to how online-based learning is so that it is faster and easier to use and the application used is SLIMS.